Ultra‐deep catalytic adsorptive desulfurization of diesel fuel using Ti‐silica gel adsorbent at low Ti‐loading. Issue 2 (26th October 2021) - Dong, Lei; Dai, Xiong; Peng, Chong; Yang, Cuiting; Li, Guoqing; Chen, Shibin; Miao, Guang; Xiao, Jing
Abstract: In this work, the effective ultra‐deep catalytic adsorptive desulfurization (CADS) using titanium‐silica gel (Ti‐SG) adsorbent at low Ti loading (<1 wt.%) was investigated. The superior CADS capacity (37.3 mg‐S/g‐A) and high TOF value (432 h −1 ) for dibenzothiophene (DBT) of Ti‐SG adsorbent were achieved at Ti loading of 0.6% with high dispersion and low titanium coordination. The rate equation of catalytic DBT oxidation was described as r DBT = N 2 k K CHP DBT, where the TiOOR was determined as the intermediate to enable the DBT oxidation to form the corresponding sulfone (DBTO2 ). The effectiveness of CADS using Ti‐SG adsorbents was verified in real diesels with varied sulfur concentrations and O/S ratios in the dynamic adsorption and multicycle regeneration. This work provides insights on using low‐cost bifunctional catalytic adsorbents at low Ti loadings for effective CADS to realize ultra‐deep desulfurization of transportation fuels.